An analytical study of the role of selected metal ions in bone and joint diseases - Furst, Alexandra (1995)
Metal ions play a major role in a wide range of biological processes in the human body. Metal ions in low-molecular weight complexes are of particular interest because of their greater 'mobility' and 'reactivity' compared to the high-molecular weight protein-bound metal ions. In this project, low-molecular weight metal ions encountered in vivo due to bone and joint disease are studied, namely gold, titanium and iron metal ions.